Complicity and the law of state responsibility - Aust, Helmut Philipp, 1980- (Cambridge : Cambridge University Press, 2011)
'This systematic analysis of State complicity in international law focuses on the rules of State responsibility. Combining a theoretical perspective on complicity based on the concept of the international rule of law with a thorough analysis of international practice, Helmut Philip Aust establishes what forms of support for wrongful conduct entail responsibility of complicit States and sheds light on the consequences of complicity in terms of reparation and implementation. Furthermore, he highlights how international law provides for varying degrees of responsibility in cases of complicity, depending on whether peremptory norms have been violated or special subject areas such as the law of collective security are involved. The book shows that the concept of State complicity is firmly grounded in international law, and that the international rule of law may serve as a conceptual paradigm for today's international legal order'--
Machine generated contents note: 1. Introduction; 2. Complicity between bilateralism and community interest; 3. Complicity and the international rule of law; 4. Complicity in customary international law; 5. The concept of complicity in Article 16 ASR; 6. The consequences of complicity; 7. Complicity and aggravated responsibility; 8. A network of rules on complicity; 9. Concluding observations.
Includes bibliographical references and index.
Keywords: United Nations. -- International Law Commission; Government liability (International law); International criminal law; Accomplices